Forming professionsl competence of teachers with using the multimedia capabilities - Mirsaliyeva N.B. , Mirsaliyeva N.B. (Рroblems of engineering and professional education, 2022)
Determination of the purpose, content, methods, pedagogical conditions and opportunities of use of multimedia capabilities of the future teachers of the fine arts for the purpose of teaching to the subject of the art of creation and use of multimedia tools. In today’s educational institutions, much attention is paid to the use of computers in professional development. During the educational process, training and testing programs are used in various disciplines.